Исследование процесса обтекания корпусов легкобронированых машин ударной волной - Васильев, Антон Юрьевич (НТУ "ХПИ", 2009)
The methods of shock wave flow analysis of lightly armored vehicles hulls was developed
Research of process of shock wave flow around the lightly armored vehicles hulls
Keywords: колесно-гусеничные машины; давление; фронт волны; корпус; движитель; колесо